Answer:
1/3
Step-by-step explanation:
B. As the x-values increase, the y- valuebtend to decrease.
Answer:
![x = \sqrt{58}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Csqrt%7B58%7D%20)
Step-by-step explanation:
first, you should draw a line to separate the triangle from the rectangle
You can get the height if the triangle by saying 16-9
This will give you 7
The base of the triangle is 3 because the opposite side is given and the opposite sides of a rectangle are equal
Now that we have the measurements of the triangle we can use the Pythagorean theorem
![{c}^{2} = {a}^{2} + {b}^{2}](https://tex.z-dn.net/?f=%20%7Bc%7D%5E%7B2%7D%20%20%3D%20%20%7Ba%7D%5E%7B2%7D%20%20%2B%20%20%20%7Bb%7D%5E%7B2%7D%20)
![{x}^{2} = {7}^{2} + {3}^{2}](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%3D%20%20%7B7%7D%5E%7B2%7D%20%20%2B%20%20%7B3%7D%5E%7B2%7D%20)
![{x}^{2} = 49+ 9](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%3D%2049%2B%209)
![{x}^{2} = 58](https://tex.z-dn.net/?f=%20%7Bx%7D%5E%7B2%7D%20%20%3D%2058)
![x = \sqrt{58}](https://tex.z-dn.net/?f=x%20%3D%20%20%5Csqrt%7B58%7D%20)
(5 + x) / 6 = -1....multiply both sides by 6, cancelling out the 6 on the left side
5 + x = -1 * 6
5 + x = -6
x = -6 - 5
x = -11
Answer:
x2=−8(y−2)
Step-by-step explanation:
Parabola is a locus of a point which moves at the same distance from a fixed point called the focus and a given line called the directrix.
Let P(x,y) be the moving point on the parabola with
focus at S(h,k)= S(0,0)
& directrix at y= 4
Now,
|PS| = √(x-h)2 + (y-k)2
|PS| = √(x-0)2 + (y-0)2
|PS| = √ x2 + y2
Let ‘d’ be the distance of the moving point P(x,y) to directrix y- 4=0
- d= |ax +by + c|/ √a2 + b2
- d= |y-4|/ √0 + 1
- d= |y-4| units.
equation of parabola is:
- |PS| = d
- √ x2 + y2 = |y-4|
Squaring on both sides, we get:
- x2 + y2 = (y-4)2
- x2 + y2 = y2 -8y + 16
- x2 = - 8y + 16
- x2 = -8 ( y - 2)
This is the required equation of the parabola with focus at (0,0) and directrix at y= 4.